Phenotypic patient profiling for improved implementation of guideline-directed medical therapy: An exploratory analysis in a large real-world chronic heart failure cohort - Radhoe, Sumant P.; Clephas, Pascal R. D.; Linssen, Gerard C. M.; Oortman, Remko M.; Smeele, Frank J.; Van Drimmelen, Annemarie A.; Schaafsma, Henk-Jan; Westendorp, Paul H.; Brunner-La Rocca, Hans-Peter; Brugts, Jasper J. (Frontiers in Pharmacology, 2023)
Aims Implementation of guideline-recommended pharmacological treatment in heart failure (HF) patients remains challenging. In 2021, the European Heart Failure Association (HFA) published a consensus document in which patient profiles were created based on readily available patient characteristics and suggested that treatment adjusted to patient profile may result in better individualized treatment and improved guideline adherence. This study aimed to assess the distribution of these patient profiles and their treatment in a large real-world chronic HF cohort. Methods and results The HFA combined categories of heart rate, blood pressure, presence of atrial fibrillation, chronic kidney disease, and hyperkalemia into eleven phenotypic patient profiles. A total of 4,455 patients with chronic HF and a left ventricular ejection fraction ≤40% with complete information on all characteristics were distributed over these profiles. In total, 1,640 patients (36.8%) could be classified into one of the HFA profiles. Three of these each comprised >5% of the population and consisted of patients with a heart rate >60 beats per minute with normal blood pressure (>90/60 mmHg) and no hyperkalemia. Conclusion Nearly forty percent of a real-world chronic HF population could be distributed over the eleven patient profiles as suggested by the HFA. Phenotype-specific treatment recommendations are clinically relevant and important to further improve guideline implementation.